Coupled stress-suction changes in the Callovo-Oxfordian claystone - Braun Philipp; Delage Pierre; Ghabezloo Siavash; Talandier Jean (E3S Web of Conferences, 2023)
Some (saturated) claystones, considered as host rocks for deep radioactive waste disposal, are sensitive to drying and wetting. Wetting may result in swelling and damage during the resaturation of specimens for mechanical testing. Given that, due to evaporation, specimens may have lost some pore water during coring, transport, storage and trimming prior to lab testing, it is required to re-saturate them by reinjecting the evaporated water content, compressing the pore space under constant water content, or by using a combination of both. It is important to characterize the hydromechanical processes involving suction changes under total stress loading in order to adapt preparation methods and minimize sample disturbances. We present a novel experimental setup to test claystone specimens under isotropic compression at constant water content, while measuring suction, and we discuss the data of three specimens testedat different initial suctions and degrees of saturation. Interestingly, the path followed in the (decreased) suction vs (increased) total confining stress diagram was observed to be close to the Gens-Alonso “Neutral Line” (a line inclined of 45° in a suction/mean total stress diagram, illustrating similar effects of changes of both variables). In other words, even in close to saturated conditions, changes in confining stress resulted in comparable changes in suction. The data obtained indicate that applying a total stress of 12.2 MPa during resaturation keeps the material on the compressive side of the Neutral Line, limiting swelling-induced sample disturbance.